Analisis Pendapatan dan Efisiensi Teknis Usahatani Ubi Jalar di Kecamatan Ampek Angkek, Kabupaten Agam Provinsi Sumatera Barat - Angelia Leovita; Ratna Winandi Asmarantaka; Heny Kuswanti Suwarsinah Daryanto (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
Production of commodity determined by effectiveness allocation of input. The level of input allocation will give impact to production and then farm income. This study was aimed to analyze the income of sweet potato farm, to identify factors those are effect the production of sweet potato, to analyze technical efficiency and factors of technical inefficiency of sweet potato’s farm. The data was gather from 40 sweet potato farmers in Ampek Angkek district regency of Agam West Sumatra. The result showed that the income of sweet potato farmers were IDR 24,659,314.18 with R/C ratio 1.8. The R/C ratio indicated that sweet potato farm was still feasible and profitable to be cultivate. Factors that effect the production of sweet potato were seeds, organic fertilizer, labor in the family, and labor outside the family. The average of technical efficiency rate was 0.85, which means that productivity of sweet potato farm achieved 85 percent from the maximum level. Meanwhile, the inefficiency can be reduce by membership of farm group, age, and land tenure.